Physical alterations induced by compaction of a coarse silty Dark Red Latosol - Borges, Elias Nascentes (1999)
This research was conducted with the objective of studying physical alterations due to different levels of compaction in a coarse silty Dark Red Latosol (Oxisol). Compaction was obtained through a hydraulic press and bulk densities were checked in a gamma ray apparatus. Using soil mechanical equations, it was observed that the application of a strength over the soil reduced the total porosity and the aeration space, while increased in the same proportion the solid and water volumetric content.